Non-HDL Estimation Methods: Advancing Cardiovascular Disease Prediction - Akbar, Md; Jha, Deepak; Ali, Hasan; Ahmad, Tasneem (Indian Journal of Pharmacy Practice)
Cardiovascular Disease (CVD) remains a global health concern, with dyslipidemia playing a significant role in its development. Traditional approaches to assessing CVD risk have primarily focused on individual lipid components, notably Low-Density Lipoprotein cholesterol (LDL-c). However, these approaches exhibit limitations, particularly when applied to populations with hypertriglyceridemia and metabolic disorders. An alternative, non-High-Density Lipoprotein cholesterol (non-HDL-c), which is calculated as the difference between total cholesterol and High-Density Lipoprotein cholesterol (HDL-c), has emerged as a superior biomarker for evaluating CVD risk. Non-HDL-c encompasses all lipoproteins associated with atherosclerosis, including those rich in triglycerides, offering a more comprehensive perspective on atherogenic burden. This biomarker possesses several advantages, including a robust correlation with atherosclerosis, consistent measurements under diverse laboratory conditions, and suitability for non-fasting samples. Most importantly, non-HDL-c exhibits superior predictive capabilities for cardiovascular events when compared to LDL-c. This review underscores the evolution of lipid assessment, elucidates the pathophysiological foundations of non-HDL-c, and underscores its central role in contemporary cardiovascular risk evaluation. Furthermore, it delves into the potential of non-HDL-c in guiding treatment decisions and enhancing patient outcomes, thus emphasizing its crucial role in the battle against CVD
Keywords: Cardiovascular disease; Dyslipidemia; Non-high-density lipoprotein cholesterol; Atherosclerosis; Risk assessment; Cholesterol management